Faktor-faktor yang mempengaruhi Keputusan Investasi Sektor Industri Pariwisata - Rantung, Danny Ivan (JBE (Journal of Business and Economics); Volume 2 No.1, 2003 JBE UNKLAB, 2003)
The rate of Return on Investment (ROI) on Capital Expenditure in tourism industry sector still influence by some factors with uncertainty elements. That’s why investment decision needs a nature consideration particularly concerning in risk and benefit in the long run or in the future. This research in conducted order to find out if there is any correlation between investment decision in tourism industry sector and the company’s  pay-back period, capital structure, and business risk. Independent variables of the present research are pay-back period (XI), capital structure (X2), and business risk (X3). Where as dependent variable is investment decision in tourism industry sector (Y). Analysis model of the present research is linear probability model. The result is showed that variables pay-back period and business risk have a strong correlations with investment decision in tourism industry sector.